Findings from the Hispanic Community Health Study/Study of Latinos on the Importance of Sociocultural Environmental Interactors: Polygenic Risk Score-by-Immigration and Dietary Interactions - McArdle, Cristin E.; Bokhari, Hassan; Rodell, Clinton C.; Buchanan, Victoria; Preudhomme, Liana K.; Isasi, Carmen R.; Graff, Mariaelisa; North, Kari; Gallo, Linda C.; Pirzada, Amber; Daviglus, Martha L.; Wojcik, Genevieve; et al. (Frontiers in Genetics, 2021)
INTRODUCTION: Hispanic/Latinos experience a disproportionate burden of obesity. Acculturation to US obesogenic diet and practices may lead to an exacerbation of innate genetic susceptibility. We examined the role of gene-environment interactions to better characterize the sociocultural environmental determinants and their genome-scale interactions, which may contribute to missing heritability of obesity. We utilized polygenic risk scores (PRS) for body mass index (BMI) to perform analyses of PRS-by-acculturation and other environmental interactors among self-identified Hispanic/Latino adults from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). METHODS: PRSs were derived using GWAS weights from a publicly available, large meta-analysis of European ancestry samples. Generalized linear models were run using from a set of a priori acculturation-related and environmental factors measured at visit 1 (2008-2011) and visit 2 (2014-2016) in an analytic subsample of 8,109 unrelated individuals with genotypic, phenotypic and complete case data at both visits. We evaluated continuous measures of BMI, and Waist to Hip ratio. All models were weighted for complex sampling design, and run combined and sex-stratified. RESULTS: Overall, we observed a consistent increase of BMI with greater PRS across both visits. We found the best-fitting model adjusted for top 5 principal components of ancestry, sex, age, study site, Hispanic/Latino background genetic ancestry group, sociocultural factors and PRS interactions with age at immigration, years since first arrival to the US, (p<0.0104), and healthy diet (p<0.0036) and explained 16% of the variation in BMI. For every 1 SD increase in PRS, there was a corresponding 1.10 kg/m2 increase in BMI (p<0.001). When these results were stratified by sex, we observed that this 1 SD effect of PRS on BMI was greater for women than men (1.45 versus 0.79kg/m2 , p<0.001). DISCUSSION: We observe that age at immigration, and the adoption of certain dietary patterns may play a significant role in modifying the effect of genetic risk on obesity. Careful consideration of sociocultural and immigration-related factors should be evaluated. The role of non-genetic factors, including the social environment, should not be overlooked when describing the performance of PRS or for promoting population health in under-studied populations in genomics.